2010
DOI: 10.1073/pnas.1011548107
|View full text |Cite
|
Sign up to set email alerts
|

Highly aneuploid zebrafish malignant peripheral nerve sheath tumors have genetic alterations similar to human cancers

Abstract: Aneuploidy is a hallmark of human cancers, but most mouse cancer models lack the extensive aneuploidy seen in many human tumors. The zebrafish is becoming an increasingly popular model for studying cancer. Here we report that malignant peripheral nerve sheath tumors (MPNSTs) that arise in zebrafish as a result of mutations in either ribosomal protein (rp) genes or in p53 are highly aneuploid. Karyotyping reveals that these tumors frequently harbor near-triploid numbers of chromosomes, and they vary in chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 39 publications
3
36
0
1
Order By: Relevance
“…Groundbreaking work by Amsterdam et al (88) has revealed that many genes encoding components of the ribosome act as haploinsufficient tumor suppressors in zebrafish. Follow-up studies have revealed that the MPNSTs that form from a loss of ribosomal genes exhibit a loss of p53 expression and are highly aneuploid (89)(90)(91). Recent work by Provost et al (92) showed that ribosomal gene rpl36 restrains Kras G12V -induced pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Groundbreaking work by Amsterdam et al (88) has revealed that many genes encoding components of the ribosome act as haploinsufficient tumor suppressors in zebrafish. Follow-up studies have revealed that the MPNSTs that form from a loss of ribosomal genes exhibit a loss of p53 expression and are highly aneuploid (89)(90)(91). Recent work by Provost et al (92) showed that ribosomal gene rpl36 restrains Kras G12V -induced pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several mutations in p53 have now been identified, including M214K 17 , N168K 17 and I166T 67 . These zebrafish p53 mutants are susceptible to a number of heritable cancers, most prominently malignant peripheral nerve sheath tumours (MPNSTs), which are highly aneuploid 68 . In many respects, the p53-I166T mutation closely models Li–Fraumeni syndrome, and because p53 is inactivated or dysfunctional in most human cancers, this provides a genetic background on which to functionally test cooperation with candidate oncogenes.…”
Section: Zebrafish As a Cancer Modelmentioning
confidence: 99%
“…Very recently, after strictly examining zebrafish malignant peripheral nerve sheath tumors (MPNST) that were induced by ribosomal protein ( rp ) and tp53 mutations, we revealed that these tumors are highly aneuploid, and that the aneuploid chromosomes show preferential presentations within a tumor and among fish tumors. For example, within a single fish tumor there is often preferential overrepresentation of chromosome 25 with simultaneous underrepresentation of chromosome 15 (Zhang et al, 2010). This finding is very similar with the aneuploidy chromosomes in human solid tumors (Wolman, 1986).…”
Section: Animal Models Of Human Cancersmentioning
confidence: 99%